2019
DOI: 10.4067/s0719-01072019000200063
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad del plasma rico en fibrina y membrana de colágeno en la regeneración ósea guiada.

Abstract: El objetivo de este estudio fue determinar la efectividad de dos biomateriales, el plasma rico en fibrina (PRF) y la membrana de colágeno en la regeneración ósea guiada. Materiales y método: Fueron utilizados 30 cobayos adultos machos entre 900 a 1100 g. divididos en tres grupos de 10 cobayos cada uno (Grupo A: Control, grupo B: Membrana de colágeno y grupo C: Plasma rico en fibrina). A cada grupo se le creó un defecto óseo mandibular unilateral de 2mm. Al grupo A no se colocó un biomaterial, en los grupos B y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Randomized clinical trials have shown that the use of PRF leads to periodontal repair, with statistically conrmed superior results for intrabony defects than when PRF is not used. When using PRF, repotentiation and increased effective performance of biomaterials such as bone gras or collagen barrier membranes are shown, in addition to periodontal regeneration of intrabony defects (53,61). A case described by Miron, et al (53) showed results of the potential for tissue repair using PRF in furcation defects.…”
Section: Prf In Intrabony Defect Regenerationmentioning
confidence: 99%
“…Randomized clinical trials have shown that the use of PRF leads to periodontal repair, with statistically conrmed superior results for intrabony defects than when PRF is not used. When using PRF, repotentiation and increased effective performance of biomaterials such as bone gras or collagen barrier membranes are shown, in addition to periodontal regeneration of intrabony defects (53,61). A case described by Miron, et al (53) showed results of the potential for tissue repair using PRF in furcation defects.…”
Section: Prf In Intrabony Defect Regenerationmentioning
confidence: 99%
“…La función principal de la membrana oclusiva es mantener el defecto aislado de células y tejido no osteogénico, además de estimular o permitir la llegada y alojamiento de osteoblastos y otros factores estimulantes de la regeneración en la zona del defecto. En comparación a la membranas no reabsorbibles, las membranas de colágeno cumplen con criterios que aseguran 51 una adecuada regeneración ósea al permitir un mejor sellado del defecto, tener una fácil manipulación y poseer una estructura que en su parte exterior impide el alojamiento de células y tejido no osteogénico y estimula la llegada de células osteogénicas [7][8][9][10] .…”
Section: Introductionunclassified
“…The human body has a limited capacity to regenerate bone tissue, which is why regenerative techniques involving different biomaterials are constantly being tested to develop a tissue that is the closest in its anatomical structure and functionality to the previous one. 1 One of the most prevalent oral diseases is periodontal disease. Due to the its high prevalence, there is consensus that the approach to treat periodontal conditions must be accompanied by a focus on public health.…”
Section: Introductionmentioning
confidence: 99%